Implementasi Komik Biologi sebagai Media untuk Meningkatkan Penguasaan Konsep dan Alat Ukur Kreativitas Mahasiswa pada Materi Organel Pengubah Energi - Nur Subkhi (Universitas Wiralodra, 2017)
This study aims to determine increased mastery of concept and the creativity ofcollege students through the implementation of biological comics on matter of energyconverters organelle. Research is Quasi Experimental with Nonequivalent Control GroupDesign. The population in this study is all college students semester III, study programe ofbiology education, level S1, Wiralodra University. Sample research as much as two (2)classes. experimental class and control classes. Sampling technique with nonprobabilitysampling. This type of sampling is saturated (census). The results of data analysis obtainedan average increased mastery of the concept classroom experiments 0.28 categoriesinclude an increase in the low, control class and 0.07 categories include an increase inlow. Score shows creativity 2 categories of creativity good and 7 categories of creativityenough. Hypothesis test using the test-t obtained value thitung = 3344 and ttabel = 1696.Therefore thitung > ttabel then thank Ha, this means that there is a significant differencein the ability of the final mastery student between classes that use media comics biologywith the class without using media comics biology. Based on a t-test and score ofcreativity then the implementation of biological comics can increase mastery of conceptand bring up the creativity of college students on matter of energy converters organelle.